Resolution Analysis of Vortex Electromagnetic Radar Imaging - Jianqiu WANG; Kang LIU; Yu WANG; Hongqiang WANG (Leida xuebao, 2021)
The vortex ElectroMagnetic (EM) wave, whose phase wavefront is modulated by the Orbital Angular Momentum (OAM), has received immense attention, especially in the field of forward-looking radar imaging. Based on the fundamental principle and imaging method of the vortex EM radar, the azimuth resolution was studied in this paper. First, the circumstance of considering the Bessel amplitude term was analyzed, indicating that the azimuth resolution was determined by the effective scope of OAM modes. Then, an effective method for calculating the scope of OAM modes was proposed, including the expressions of azimuth resolution, spatial resolution, and super-resolution were characterized. Finally, the fundamental resolution performance with different influencing factors was analyzed via simulations. The analysis showed that changing the wavelength aperture ratio and imaging elevation could increase the effective scope of OAM modes, which improved the azimuth resolution. Through data fitting, the approximate expressions of the effective scope of OAM modes and the resolution of the super-real aperture radar with respect to the wavelength aperture ratio and imaging elevation were obtained separately, providing a reference for the parameters design and optimization of vortex EM wave radar.